Bioenergetic signatures of neurodevelopmental regression - Frye, Richard E.; McCarty, Patrick J.; Werner, Brianna A.; Rose, Shannon; Scheck, Adrienne C. (Frontiers in Physiology, 2024)
Background: Studies have linked autism spectrum disorder (ASD) to physiological abnormalities including mitochondrial dysfunction. Mitochondrial dysfunction may be linked to a subset of children with ASD who have neurodevelopmental regression (NDR). We have developed a cell model of ASD which demonstrates a unique mitochondrial profile with mitochondrial respiration higher than normal and sensitive to physiological stress. We have previously shown similar mitochondrial profiles in individuals with ASD and NDR.Methods: Twenty -six ASD individuals without a history of NDR (ASD-NoNDR) and 15 ASD individuals with a history of NDR (ASD-NDR) were recruited from 34 families. From these families, 30 mothers, 17 fathers and 5 typically developing (TD) siblings participated. Mitochondrial respiration was measured in peripheral blood mononuclear cells (PBMCs) with the Seahorse 96 XF Analyzer. PBMCs were exposed to various levels of physiological stress for 1 h prior to the assay using 2,3-dimethoxy-1,4-napthoquinone.Results: ASD-NDR children were found to have higher respiratory rates with mitochondria that were more sensitive to physiological stress as compared to ASD-NoNDR children, similar to our cellular model of NDR. Differences in mitochondrial respiration between ASD-NDR and TD siblings were similar to the differences between ASD-NDR and ASD-NoNDR children. Interesting, parents of children with ASD and NDR demonstrated patterns of mitochondrial respiration similar to their children such that parents of children with ASD and NDR demonstrated elevated respiratory rates with mitochondria that were more sensitive to physiological stress. In addition, sex differences were seen in ASD children and parents. Age effects in parents suggested that that mitochondrialmitochondria of older parents were more sensitive to physiological stress.This study provides further evidence that children with ASD and NDR may have a unique type of mitochondrial physiology that may make them susceptible to physiological stressors. Identifying these children early in life before NDR occurs and providing treatment to protect mitochondrial physiology may protect children from experiencing NDR. The fact that parents also demonstrate mitochondrial respiration patterns similar to their children implies that this unique change in mitochondrial physiological may be a heritable factor (genetic or epigenetic), a result of shared environment, or both.